Development of palm oil-based fly ash powder-binder system for three-dimensional printing - Mohd Zain, Norhidayah (2010)
Three-dimensional printing (3DP) is one of the techniques in rapid prototyping (RP) technology which creates parts directly from graphical data computer and it is being widely used in diverse areas. However, the cost of the 3DP material is high and limited to a number of choices that can be used due to the restricted capabilities of the existing binder. This research aims to investigate the potential of the new powder-binder system for palm oil-based fly ash (POFA) for 3DP applications. The newly proposed material is a type of powder-binder system containing POFA powder, maltodextrin and polyvinyl alcohol (PVA) which was prepared thoroughly by three different techniques; mechanical mixing, ball milling and solution blending process. Certain mass percentage of POFA powder-binder system was successfully fabricated as a product of the 3DP of which distilled water was used as the binding material and followed by post-treatment with the Z Max solution in order to further improve their mechanical properties. The experimental results show that, by using solution blending process during material preparation of the POFA powder-binder system is able to achieve good tensile strength and surface quality with mean values of 6.65MPa and 12.05µm, respectively. However, the preparation of POFA powderbinder system by using the mechanical mixing method show good flexural strength